Red Blood Cell-Mediated S-Nitrosohemoglobin-Dependent Vasodilation: Lessons Learned from a β-Globin Cys93 Knock-In Mouse - Premont, Richard T; Reynolds, James D; Zhang, Rongli; Stamler, Jonathan S (Antioxidants & redox signaling, 2021)
Red blood cell (RBC)-mediated vasodilation plays an important role in oxygen delivery. This occurs through hemoglobin actions, at least in significant part, to convert heme-bound nitric oxide (NO) (in tense [T]/deoxygenated-state hemoglobin) into vasodilator S-nitrosothiol (SNO) (in relaxed [R]/oxygenated-state hemoglobin), convey SNO through the bloodstream, and release it into tissues to increase blood flow. The coupling of hemoglobin R/T state allostery, both to NO conversion into SNO and to SNO release (along with oxygen), under hypoxia supports the model of a three-gas respiratory cycle (O /NO/CO ). Oxygenation of tissues is dependent on a single, strictly conserved Cys residue in hemoglobin (βCys93). Hemoglobin couples SNO formation/release at βCys93 to O binding/release at hemes ("thermodynamic linkage"). Mice bearing βCys93Ala hemoglobin that is unable to generate SNO-βCys93 establish that SNO-hemoglobin is important for R/T allostery-regulated vasodilation by RBCs that couple blood flow to tissue oxygenation. The model for RBC-mediated vasodilation originally proposed by Stamler in 1996 has been largely validated: SNO-βCys93 forms , dilates blood vessels, and is hypoxia-regulated, and RBCs actuate vasodilation proportionate to hypoxia. Numerous compensations in βCys93Ala animals to alleviate tissue hypoxia (discussed herein) are predicted to preserve vasodilatory responses of RBCs but impair linkage to R/T transition in hemoglobin. This is borne out by loss of responsivity of mutant RBCs to oxygen, impaired blood flow responses to hypoxia, and tissue ischemia in βCys93-mutant animals. SNO-hemoglobin mediates hypoxic vasodilation in the respiratory cycle. This fundamental physiology promises new insights in vascular diseases and blood disorders.